OX40L/OX40 Signal Promotes IL-9 Production by Mucosal MAIT Cells During Helicobacter pylori Infection - Ming, Siqi; Zhang, Mei; Liang, Zibin; Li, Chunna; He, Jianzhong; Chen, Peiyu; Zhang, Shunxian; Niu, Xiaoli; Deng, Shimei; Geng, Lanlan; Zhang, Guoliang; Gong, Sitang; et al. (Frontiers in Immunology, 2021)
Mucosal associated invariant T (MAIT) cells play a critical role in Helicobacter pylori (H. pylori)-induced gastritis by promoting mucosal inflammation and aggravating mucosal injuries (1, 2). However, the underlying mechanism and key molecules involved are still uncertain. Here we identified OX40, a co-stimulatory molecule mainly expressed on T cells, as a critical regulator to promote proliferation and IL-9 production by MAIT cells and facilitate mucosal inflammation in H. pylori-positive gastritis patients. Serum examination revealed an increased level of IL-9 in gastritis patients. Meanwhile, OX40 expression was increased in mucosal MAIT cells, and its ligand OX40L was also up-regulated in mucosal dendritic cells (DCs) of gastritis patients, compared with healthy controls. Further results demonstrated that activation of the OX40/OX40L pathway promoted IL-9 production by MAIT cells, and MAIT cells displayed a highly-activated phenotype after the cross-linking of OX40 and OX40L. Moreover, the level of IL-9 produced by MAIT cells was positively correlated with inflammatory indexes in the gastric mucosa, suggesting the potential role of IL-9-producing MAIT cells in mucosal inflammation. Taken together, we elucidated that OX40/OX40L axis promoted mucosal MAIT cell proliferation and IL-9 production in H. pylori-induced gastritis, which may provide potential targeting strategies for gastritis treatment.